Perlindungan Hukum Pemilikan Hak Atas Tanah Bagi Warga Masyarakat Rowok di Kawasan Bisnis Pariwisata Selong Belanak, Kabupaten Lombok Tengah - Sahnan -; Zainal Asikin; L. Wira Pria Suhartana (Jatiswara, 2015)
Research result shown that: (1) the arrangement of legal protection and tribute on people’s rights to manage land resources has stated on in Article 18B of Institutional Law (UUD) 1945 (as a constitutional right), Article 28 I of UUD 1945 and Law number 19 of 1999 (considered as one of human rights). In the elucidation of Article 22 UUPA (Law of the land) has beed clarified that to own land ownership right could be throught land occupation, this way is feasible according to adat law where National land law based on adat law (according to Article 5 UUPA). (2) the implementation of legal protection toward ownership holders in Rowok case is still away from expectation, this could be seen from the way the government and security officer treated land owner such as committed an eviction, tumbled-down their house and some people who insist to stay on their land were arrested by security officer under allegation of law for entering people’s property without permission whereas they occupied the land previously as a place to stay and place to live.